Transformational Leadership of School Improvement Partner (Sipartner +) and Coaching Process in Education Development Leadership - Rahim, Hazura Abdul; Hamzah, Mohd Izham Mohd; Noor, Mohamad Yusof Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Transformational leadership attends the mission to transform the leadership and organisation. Accordingly, the School Improvement Partner (SIPartner +) employs a coaching method in the guiding process to promote school leaders to make adjustments to the organisation. Nevertheless, the SIPartner + transformation leadership practice research is inadequate. This research explores SIPartner + transformational leadership practice as a mentor in performing transformational leadership of principals and headteachers adopting a coaching approach. The study sample was comprised of 117 SIPartner + employees in the District Education Office (PPD) throughout Malaysia. Quantitative research in the form of surveys involved questionnaire management was adopted to collect data. Selection of study samples was made randomly. Data were analysed utilising SPSS version 23.0. The descriptive findings confirmed that the transformational leadership practices and coaching processes among SIPartner + are at a high level. Also, inference analysis revealed that there is a positive and significant relationship between transformational leadership practice and the coaching process. Additionally, this study designated that SIPartner + transformational leadership leads to leadership advancement among school leaders. Hence, it is recommended that the Leadership Guidance Program should be administered consistently and systematically so that it stays apposite to the contemporary hurdles and demands of the Malaysia education system.